The Hermeneutics of (Im)politeness: A Gadamerian Perspective - Nielsen, Cynthia R. (Ruch Filozoficzny, 2020)
Central to Gadamerian hermeneutics is dialogical engagement, a back and forth “play” (Spiel) among interlocutors. For Gadamer, texts as well as works of art function as interlocutors capable of addressing and making a claim upon us. However, whether engaging a human dialogue partner or a text, one must approach the other with openness, which can be understood as a hermeneutic virtue. Consequently, in order for a fruitful dialogue to occur, one must embody a specific comportment to the other. In this sense, hermeneutics exhibits a politeness of sorts. If one considers the Latin roots (politus, polire) from which we derive our English term “polite,” relevant connections with notion of refinement and being “polished” emerge. That is, to be polite is in some sense to exhibit refinement, which often comes through a process of training or even suffering. One the one hand, openness to the other involves politeness or refinement in that one demonstrates respect for the other in a genuine willingness to hear the other’s view. Such refinement has been achieved through experience (Erfahrung) and continues to be achieved through dialogical engagement with others. On the other, it is also the case that hermeneutical dialogue involves elements of impoliteness, where one transgresses social norms in order to provoke a thoughtful, self-reflective response.